(untitled) - Meisie Mangantes, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Learning from home for students in the current Covid-19 pandemic era needs teacher innovation in learning. This study aimed to explain the relationship between collective trust and teacher innovativeness in South Minahasa Regency, North Sulawesi, Indonesia. Quantitative approaches and survey methods were used in this study. The number of samples was 79 respondents. Using questionnaires for data collection and correlation analysis techniques for data processing. The results showed teachers' collective trust had a positive and significant correlation with teacher innovativeness. Likewise, the dimensions of trust in the principal, trust in peers, and trust in clients (students and parents) have a positive and significant correlation with teacher innovativeness. This article also provides a discussion of research results, conclusions.